Germline BRCA2 K3326X and CHEK2 I157T mutations increase risk for sporadic pancreatic ductal adenocarcinoma. Issue 3 (7th February 2019) - Obazee, O.; Archibugi, L.; Andriulli, A.; Soucek, P.; Małecka‐Panas, E.; Ivanauskas, A.; Johnson, T.; Gazouli, M.; Pausch, T.; Lawlor, R. T.; Cavestro, G. M.; Milanetto, A. C.; et al.
Abstract : Rare truncating BRCA2 K3326X (rs11571833) and pathogenic CHEK2 I157T (rs17879961) variants have previously been implicated in familial pancreatic ductal adenocarcinoma (PDAC), but not in sporadic cases. The effect of both mutations in important DNA repair genes on sporadic PDAC risk may shed light on the genetic architecture of this disease. Both mutations were genotyped in germline DNA from 2, 935 sporadic PDAC cases and 5, 626 control subjects within the PANcreatic Disease ReseArch (PANDoRA) consortium. Risk estimates were evaluated using multivariate unconditional logistic regression with adjustment for possible confounders such as sex, age and country of origin. Statistical analyses were two‐sided with p values <0.05 considered significant. K3326X and I157T were associated with increased risk of developing sporadic PDAC (odds ratio (ORdom ) = 1.78, 95% confidence interval (CI) = 1.26–2.52, p = 1.19 × 10 −3 and ORdom = 1.74, 95% CI = 1.15–2.63, p = 8.57 × 10 −3, respectively). Neither mutation was significantly associated with risk of developing early‐onset PDAC. This retrospective study demonstrates novel risk estimates of K3326X and I157T in sporadic PDAC which suggest that upon validation and in combination with other established genetic and non‐genetic risk factors, these mutations may be used to improve pancreatic cancer risk assessment in European populations. Identification of carriers of these risk alleles as high‐risk groups may also facilitate screening or prevention strategies for such individuals, regardless of family history. Abstract : What's new? Mutations in BRCA2 and CHEK2 are associated with susceptibility to many cancers, including pancreatic. The survival rate for pancreatic cancer remains abysmal, and early diagnostic markers are urgently needed. Here, the authors investigated the effect of a truncating BRCA2 variant (rs11571833) and a missense CHEK2 variant (rs17879961) on sporadic pancreatic ductal adenocarcinoma risk. Using data from the PANDoRA consortium, they tested a large number of samples, making this the first high‐power study to investigate these variants. Both variants, they found, increased the risk of non‐familial PDAC, and these variants may contribute to polygenic risk scores that help identify at‐risk individuals.